Readiness and Participation of Local Community for River Based Tourism Development in Sabak Awor Muar, Johor - Zuhairi, Siti Nur Aishah; Abd Rahman, Nur Hidayah; Abas, Siti Aisah; Md Sawari, Siti Salwa; Abdul Latif, Samshul Amry (CRC PRESS, ROUTLEDGE, TAYLORS & FRANCIS, 2021)
The research on river-based tourism in terms of community participation and readiness for river-based tourism development is still limited, especially in the Malaysian context. For instance, this study intends to explore the readiness and participation of local community for river-based tourism development in Sabak Awor, Muar. A qualitative approach is adopted to this study on the readiness and community participation for river-based tourism development in Sabak Awor village, Muar through the semi-structured interview questions. A total of five local residents have participated in the interview. The analyses have yielded into five main findings, namely the low level of knowledge influence local’s readiness, tourism resources presents the creation of tourism activities in the area, low involvement in participation in decision making process and planning, high involvement of community in tourism operation and management, and benefits gained in terms of economic, infrastructure of the village, and personal development of the community. This study contributes to the planning and development of river-based tourism activities. The findings are beneficial for the management of the key players in tourism industry to promote the potential of Sabak Awor village as a new tourism destination, specifically for the river-based tourism.